A new aryltetralin lignan and other phytoconstituents from Atractylis humilis. (June 2020) - Sifouane, Siham; Benabdelaziz, Imane; Benkhaled, Mohammed; Gómez-Ruiz, Santiago; Carralero, Sandra; Haba, Hamada
Abstract: Phytochemical research of the whole plant Atractylis humilis (Asteraceae family) led to the isolation of one cyclolignan, namely (8R, 7′S, 8′S)-9′- β -D-glucopyranosyl-3, 4′, 9-trihydroxy-3′, 4, 5, 5′-tetramethoxy-2, 7′-cyclolignan (1 ), together with thirteen known phytochemicals 2 –14 from the ethyl acetate and n -butanol extracts. The structures of all isolated secondary metabolites 1 –14 were elucidated by spectroscopic analysis (1D and 2D-NMR, HR-ESI-MS) and measurement of optical rotation [α]D, whereas the known compounds were described by spectral comparison data with those published in the literature. This is the first report of lignans in the genus Atractylis . Furthermore, the chemotaxonomic significance of isolates was discussed. Graphical abstract: Image 1 Highlights: Atractylis humilis L. was chemically investigated for the first time. Polyphenols were isolated from EtOAc and n -BuOH extracts. Isolated compounds have been characterized by spectroscopic methods. Lignans and C -glycosylflavones could be of significant importance for the chemotaxonomic profile of the genus Atractylis.